PENGARUH PELAYANAN, KEYAKINAN AGAMA, DAN LOKASI TERHADAP MINAT MENABUNG NASABAH PADA PT. BANK MEGA SYARIAH DI MAKASSAR - Zainal Abidin (AkMen JURNAL ILMIAH, 2015)
This study aims to determine the significance of the influence of services, religious beliefs, and the location influence the customers' interest in Bank Mega Syariah saving in Makassar.Populasi in this study were all active clients of Bank Mega Syariah in Makassar who open a savings account for January to June 2014 302 person. While the determination of the number of samples determined by using Slovin approach, in order to obtain a sample of 100 people. The data analysis technique used is multiple linear regression. The results showed bahwafaktor care facilities and services trade, religious beliefs factor, and location factors significantly influence the interest of saving the customer at Bank Mega Syariah in Makassar